2016
DOI: 10.1016/j.ymgmr.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the autoinhibitory segment comprising residues 31–60 of the prodomain of PCSK9: Possible implications for the mechanism underlying gain-of-function mutations

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) binds to the low density lipoprotein receptor (LDLR) at the cell surface and is internalized as a complex with the LDLR. In the acidic milieu of the sorting endosome, PCSK9 remains bound to the LDLR and prevents the LDLR from folding over itself to adopt a closed conformation. As a consequence, the LDLR fails to recycle back to the cell membrane. Even though it is the catalytic domain of PCSK9 that interacts with the LDLR at the cell surface, the structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The prodomain sequence is rich in acidic residues and has been suggested to play an autoinhibitory role through interaction with the basic residues in the PCSK9 catalytic domain [ 14 ]. Another possible regulatory function of the acid prodomain sequence has been proposed as around 40% of PCSK9 in plasma is associated with LDL-C particles and in vitro prodomain truncation variant lacking residues 31–52 is unable to bind LDL-C [ 207 ]. Furthermore, in cell-based experiments LDL-C particles lower the LDLR degradation activity of PCSK9 [ 91 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prodomain sequence is rich in acidic residues and has been suggested to play an autoinhibitory role through interaction with the basic residues in the PCSK9 catalytic domain [ 14 ]. Another possible regulatory function of the acid prodomain sequence has been proposed as around 40% of PCSK9 in plasma is associated with LDL-C particles and in vitro prodomain truncation variant lacking residues 31–52 is unable to bind LDL-C [ 207 ]. Furthermore, in cell-based experiments LDL-C particles lower the LDLR degradation activity of PCSK9 [ 91 ].…”
Section: Introductionmentioning
confidence: 99%
“…To more quantitatively assess the effect of the A44P mutation in full-length PCSK9, we performed a steady-state binding analysis in which fluorescent dye-labeled WT PCSK9 was incubated with LDL in the presence of increasing concentrations of unlabeled WT PCSK9 or PCSK9-A44P. For comparison purposes, we also included PCSK9 lacking the N-terminal 21 residues (⌬31-52), which is defective in LDL binding (18) and hyperactive in terms of LDLR binding/degradation (27,34). Competition binding curves showed that the PCSK9-A44P mutant had a Ͼ5-fold decrease in LDL binding affinity compared with WT PCSK9 (Fig.…”
Section: Helical Conformation Specifically Affects Pcsk9 Binding Affimentioning
confidence: 99%
“…PCSK9 is the ninth member of the protein convertase family that is synthesized as a proprotein and requires an autocatalytic cleavage to become mature [ 56 ]. The result of the cleave is a N-terminal prodomain that remains bound to the catalytic domain and inhibits convertase function [ 57 ].…”
Section: Cholesterol Metabolismmentioning
confidence: 99%